The moment of death in early modern Europe, c. 1450-1800 contested ideals, controversial spaces, and suspicious objects - Brunner, Benedikt 1986-; Christ, Martin 1991- (Brill, 2024)
"Both in our time and in the past, death was one of the most important aspects of anyone's life. The early modern period saw drastic changes in rites of death, burials and commemoration. One particularly fruitful avenue of research is not to focus on death in general, but the moment of death specifically. This volume investigates this transitionary moment between life and death. In many cases, this was a death on a deathbed, but it also included the scaffold, battlefield or death in the streets. Contributors include: Friedrich J. Becher, Benedikt Brunner, Isabel Casteels, Martin Christ, Louise Deschryver, Irene Dingel, Michaël Green, Vanessa Harding, Sigrun Haude, Vera Henkelmann, Imke Lichterfeld, Erik Seeman, Elizabeth Tingle, and Hillard von Thiessen"--
Keywords: Katholische Kirche; Geschichte 1450-1800; Brauch; Tod -- Motiv; Konfessionalisierung; Totenbett; Protestantismus; Bestattung; Sterben; Reformation; Tod; Europa; Death / Social aspects / Europe / History / 16th century; Death / Social aspects / Europe / History / 17th century; Death / Symbolic aspects / Europe / History / 16th century; Death / Symbolic aspects / Europe / History / 17th century; Aufsatzsammlung